Impact of Crypto-Mining Malware on System Resource Utilization - Berlin, K; Dhenakaran, SS (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, the whole world works in modern technology. Peoples are paying more attention to complete the process in a sophisticated way without putting the much human effort. End-user thinks that only poor knowledge about application usage leads to data security issues. But application providing companies camouflage the truth behind the name of the user sophistication. Even a small piece of a script code can make the huge data security issues. That type of problems is called cryptocurrency malware. Cryptomining malware is nothing but software code and designed to take system resources without the knowledge of authorized end users. The role of cryptomining is stealing computer’s resources with the help of auto inject of malware code in a crook way while making online communications on websites. A website owner uses these malware codes to take visitor's system utilization to gain more earning. Cryptomining malware easily injects electronic devices like computers, smart phones to increase earnings from cryptocurrency mining